Representasi Perempuan Dalam Film Boston Strangler (Analisis Wacana Jager & Maier) - Rindi Antika; Nuraida; Emi Puspita Dewi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This research is entitled "Representation of Women in the Film Boston Strangler (Discourse Analysis of Jager & Maier)". The film Boston Strangler by Matt Ruskin is a film that shows women journalists, that they are able to complete their duties as journalists in solving and finding the mastermind behind the serial murder cases in the city of Boston. because at that time they experienced sexism in the workplace. Sexism is prejudice and discrimination based on gender. This research aims to determine the representation of women in the Boston Strangler film. The research method used is a qualitative research method with primary and secondary data types and sources, primary data is the data source taken through Film Boston from the Telegram application. Secondary data was taken in the form of references such as internet books and scientific journals. The data collection techniques used are observation and documentation techniques. Meanwhile, the data analysis technique used is discourse analysis according to Jager & Maier with six stages in the process, including: making a film summary, determining characters, looking for representative conversations, forms of action, materializing objects and theorizing film themes. The results of this research show that there are female roles depicted in several film scenes such as dialogue, behavior and the characteristics presented by Loretta as a journalist at that time. Apart from that, this research shows that women are represented as strong, active and independent women in carrying out their duties as female journalists and as housewives.